2016
DOI: 10.1111/ibi.12440
|View full text |Cite
|
Sign up to set email alerts
|

Central European Greylag GeeseAnser ansershow a shortening of migration distance and earlier spring arrival over 60 years

Abstract: Global climate change can cause pronounced changes in speciesʼ migratory behaviour. Numerous recent studies have demonstrated climate‐driven changes in migration distance and spring arrival date in waterbirds, but detailed studies based on long‐term records of individual recapture or re‐sighting events are scarce. Using re‐sighting data from 430 marked individuals spanning a 60‐year period (winters 1956/1957 to 2015/2016), we assessed patterns in migration distance and spring arrival date, wintering‐site fidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…We did not detect any link between the winter NAO and the shift in the population centroid of goose and swan species that exploit farmland habitats. Previous studies at smaller spatial scales have shown that the wintering distribution of the Greylag goose is undergoing change in response to changing weather conditions (Podhrázský et al., ; Ramo et al., ). However, our results suggest that this is not the general response of other species with similar life‐history and ecological traits (after accounting for phylogenetic relatedness) such us Branta , Cygnus and other Anser species (considered as farmland species in this study, see Supporting information ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not detect any link between the winter NAO and the shift in the population centroid of goose and swan species that exploit farmland habitats. Previous studies at smaller spatial scales have shown that the wintering distribution of the Greylag goose is undergoing change in response to changing weather conditions (Podhrázský et al., ; Ramo et al., ). However, our results suggest that this is not the general response of other species with similar life‐history and ecological traits (after accounting for phylogenetic relatedness) such us Branta , Cygnus and other Anser species (considered as farmland species in this study, see Supporting information ).…”
Section: Discussionmentioning
confidence: 99%
“…Geese typically leave wetlands to feed on agricultural fields (Fox & Abraham, ), which are not counted by the IWC, and hence, important numbers of geese might be missed during the counts. This, coupled with very rapid population increases in the last four decades, may partly explain the lack of statistical significance of the large‐scale distributional changes linked to changes in weather conditions among species favouring field foraging, which have been shown to be currently ongoing in Europe (Podhrázský et al., ; Ramo et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…trophic level, body size, habitat preferences) observed across species (see Chapman et al 2011 for a review). Furthermore, given that individuals and populations can react faster to environmental changes than entire species, monitoring the responses of partially migratory species to anthropogenic activities can provide early insights into how species respond to global change (Pulido & Berthold 2010;Podhrázský et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence supports the idea that the communities of birds that spend the winter in the Mediterranean region are changing due to climate warming (Morganti and Pulido 2012). In particular, an increasing proportion of birds that would hypothetically overwinter in tropical Africa now stay all the winter in the southern part of the Mediterranean (Morganti and Pulido 2012); at the same time, many species that used to overwinter in the Mediterranean are moving their wintering range to higher latitudes and altitudes (Martín et al 2014;Tellería et al 2016;Podhrázský et al 2017;Pavón-Jordán et al 2019). Additionally, changes in the land use and management, e.g.…”
Section: Introductionmentioning
confidence: 99%